Three Dollar Mule - Clyde Robert Bulla (United States Troll Communications, 1995)
A boy finds himself the owner of a mule that likes children but is very hostile to adults--to the parents' dismay and the boy's delight, all attempts to sell the animal fail
Keywords: Realistic Fiction -- Realistic Fiction